TEACHING METHODS PREFERRED BY SCHOOL SCIENCE TEACHERS AND STUDENTS IN THEIR CLASSROOM - Tufail, Imran; Mahmood, Muhammad Khalid (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This study was designed to stipulate an image of occurring science practices in secondary schools. The main objective of this study is to investigate the types of science teaching practices that have been preferred to use by science teachers to teach science subjects. This study delimits the secondary schools of Lahore, which is the second most populated city in Pakistan. The research was conducted on a sample of 60 schools [60 science teachers and 600 students]. The researchers captured the complete list of secondary schools of Lahore from official websites and schools were selected through random technique. The most senior science teacher opted for data collection in case of more than one science teacher availability at a single school. The study adopted a survey research design and data was collected through a newly developed reliable questionnaire with Cronbach alpha = 0.95. The data was entered and analysed by using SPSS. The study result reveals that secondary school science teachers prefer lecture and discussion methods for science teaching. Significantly, science teachers are less interested in using the inquiry method and science project-based learning in their classrooms. Science teachers should adopt recommended teaching methods to develop a better understanding of science among students.